An introduction to vascular biology : (Cambridge University Press, 1998)
The concept of vascular biology has emerged and expanded rapidly over the past 25 years and with research in this area has come improved understanding of a wide range of clinical conditions. For both specialists and newcomers to the field in search of a broad overview and also for the non-specialist requiring an up-to-date insight into progress and its implications, this book provides a much needed concise resource. The multidisciplinary team of contributors cover topics ranging from normal and pathological aspects of endothelial function to the role of the vasculature in hemostasis, atherosclerosis and hypertension. This carefully illustrated and highly readable text provides both a valuable source of practical information and clear explanations of the impact of new techniques of cellular and molecular biology on recent and future developments.